1996
DOI: 10.1063/1.115658
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the refractive index of thin SiO2 films using tunneling current oscillations and ellipsometry

Abstract: We use Fowler–Nordheim tunneling current oscillations to accurately determine the thicknesses of ultrathin SiO2 films, and with the thicknesses as input, we employ precision single wavelength ellipsometry to determine the real part of the refractive index for thin SiO2 films in the range of 4–6 nm. An average value for this refractive index was found to be 1.894±0.110. This value is shown to yield SiO2 thicknesses to an accuracy of ±0.1 nm. A SiO2 thickness-refractive index interpolation formula for the thin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 2 publications
0
37
3
Order By: Relevance
“…The increase in refractive index to values up to n = 1.8, as predicted by several studies, [54][55][56] is highly unlikely for native oxide layers as polymer dewetting studies have shown via an indirect way: 24 Thin liquid polystyrene (PS) films prepared on Si wafers with native oxide layers (D SiO = 2.4 nm) were unstable and dewetted spinodally. Since this process is driven by the minimization of the free energy determined by the vdW potential 8,66 the refractive indexes of the oxide cannot be higher than the one of PS (≈ 1.59), as shown by Eq.…”
Section: Properties Of Thin Native Oxide Layersmentioning
confidence: 91%
See 1 more Smart Citation
“…The increase in refractive index to values up to n = 1.8, as predicted by several studies, [54][55][56] is highly unlikely for native oxide layers as polymer dewetting studies have shown via an indirect way: 24 Thin liquid polystyrene (PS) films prepared on Si wafers with native oxide layers (D SiO = 2.4 nm) were unstable and dewetted spinodally. Since this process is driven by the minimization of the free energy determined by the vdW potential 8,66 the refractive indexes of the oxide cannot be higher than the one of PS (≈ 1.59), as shown by Eq.…”
Section: Properties Of Thin Native Oxide Layersmentioning
confidence: 91%
“…These findings were later on confirmed by other studies. 55,56 Experimental support for the double layer model, viz. the observation of an interfacial transition layer, is also given by previous studies.…”
Section: Double Layer Modelmentioning
confidence: 99%
“…3 was used to calculate the refractive index n by taking into account the optical constants of the strained layer and of all respective interfacial regions. The value n = 1.55 obtained by this calculation is smaller than described by published curves on the n(d ox ) relationship in ultrathin thermal silicon oxides [17,18]. Upon etching, the measured parabolae, shown in Fig.…”
Section: Discussionmentioning
confidence: 75%
“…13, are fitted using n, d ox pairs. According to [17,18], an increase of the refractive index was determined towards the silicon interface. The slope, however, is smaller with a maximum value of n = 1.80 at etch step 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers report elevated measurements of refractive index when simple models are applied to ultrathin films (e.g. Hebert et al ., 1996). In Fig.…”
Section: Resultsmentioning
confidence: 99%